Dynamic resilience analysis of fire-affected forest landscapes using multi-sensor spectral indicators (PaF): Research note - Pérez-Cabello, Fernando (Geographicalia, 2023)
The project "Dynamic analysis of the resilience of forest landscapes affected by fire using multisensor spectral indicators (PaF)" with code [PID2020-118886RB-I00], was awarded in the call for R+D+i projects, modality, Generation of knowledge and Research Challenges in 2020. The main objective of the project is to design a methodology, through the identification and integration of multisensor spectral indicators, that allows for the appropriate interpretation of resilience properties, taking into account different spectral diagnostic vectors related to the structure, phenology, floristic composition and eco-physiological functions of colonising communities.